3T2R Parallel Mechanism Type Synthesis based on GF Set Theory - Jie Jingbin; Cao Yi; Yu Jinghu; Ma Yao; Chen Genlu (Jixie chuandong)
Aiming at a kind of 3T2R parallel mechanism used in the industrial application,the method of parallel mechanism type synthesis based on GFset configuration theory is proposed,the specific steps of the 3T2R parallel mechanism type synthesis are given. Combining with the specific parameter,the final selection of 3T2R parallel mechanism with determined motion features is filtered. The 3-PPPR1 R2 is selected as the research object,the kinematics and dynamics analysis of the mechanism is carried out by using ADAMS,and the correctness of the 3T2R parallel mechanism based on the theory of GFset configuration in parallel mechanism is verified.